Agrupamentos de amostras circulares em função das unidades de solo - Campos, Sérgio [UNESP]; Pissarra, Teresa Crisitna Tarlé [UNESP]; Traficante, Daniela Polizeli [UNESP]; Carrega, Elen Fittipaldi Brasílio [UNESP]; Zanata, Marcelo [UNESP]; dos Reis, Fabiana Camargo [UNESP] (My University, 2014)
The objective of the study was to analyze the features of the relief through the variables: maximum altitude (HM); mean altitude (Hmd); minimum altitude (Hm); altitude range (H); average slope length (CVm); minimum length of run-off (Cd) and average steepness of circular samples (I) of the Capivara River Watershed - Botucatu (SP). A total of 4 circular samples were obtained per unit of soil (Quartzipsamment alfisol oxisol - RQ, Udox - LVA and Udorthent - RL). Multivariable analysis and aerial color photographs of 2000, Brazilian Chart and Soil Chart of Botucatu city- SP were used for data analyses. Soil differentiation was performed using the Student-t Test for analyzes of orthogonal contrasts among means of the three soils and analysis of groupings and major components. The grouping analysis of the variables of relief differentiated 75% of LVA and 100% of RL and RQ soil circular samples. The most efficient parameters of relief for differentiation of soils according to their order of importance were as follows: HM, Hm, Hmd and H.
Groupings of circular samples as a function of soil units
Keywords: Multivariable analysis; Relief; Watershed